Application of Rapid Application Development Method to Design E-Commerce Systems in National Expedition Company to Increase Marketing Effectiveness - Pramudito, Dendy K; S.Pettalongi, Sagaf; Risal Tawil, Muhamad; A, Hermila; Zein, Afrizal (Jurnal Informasi dan Teknologi, 2024)
This research aims to find out how to design a B2C, online-based e-commerce reservation system for companies. In this research, the data collection methods applied include observation, interviews, and a literature study. The system development process uses the RAD (Rapid Application Development) model and UML modeling tools. The development stages consist of requirement planning, design workshops, and implementation. Based on the research results, it was found that the existence of this B2C e-commerce system can help the public find out information about hotels in real time, find out the condition of room availability, and make room reservations online anytime and anywhere via the web. This system consists of customer registration, room reservations, payments, expense input, and viewing monthly income and expense reports. This e-commerce system makes it easier for customers to make room reservations and helps managers monitor the occupancy rate in the form of the ratio of the number of customers who make room reservations to the total number of rooms in the company through the visitor list view menu, which displays a list of the number of rooms and the number of visitors who are staying overnight. This system makes it easier for managers to view reports on total monthly income and total expenses by selecting the menu to view report data on total income and total monthly expenses.